A case report of neonatal incontinentia pigmenti complicated by severe cerebrovascular lesions in one of the male monozygotic twins - Lin, Xiaofeng; Zhang, Wei; Zhou, Ping (Frontiers in Pediatrics, 2024)
Background: This article firstly reports a case of neonatal incontinentia pigmenti only onset in one of the male monozygotic twins with characteristic skin lesions after birth followed by severe cerebrovascular lesions. Case presentation: A male, the first one of monozygotic twins, was born with multiple yellow pustules all over the body, repeated new herpes at different sites during the course of the disease, aggravated by fusion, warty crusts, and hyperpigmentation, and biopsy pathology suggested eosinophilic spongiform edema of the skin; peripheral blood eosinophils were significantly elevated; brain magnetic resonance imaging revealed diffuse multiple cystic and lamellar abnormal signal areas in the left frontal and parietal lobes. On day 30, the infant showed neurological symptoms such as poor response and apnea, and emergency cranial computed tomography revealed abnormal changes in the left cerebral hemisphere and bilateral cerebellum. After admission, he was given potassium permanganate bath and topical mupirocin for one month, and the skin abnormalities improved. He was treated with mechanical ventilation and vasoactive drugs for 2 days after the cerebrovascular accident, and died the same day after the parents chose hospice care. No deletion variants or point mutations were detected in subsequent genetic tests, and chromosomal copy number variation tests revealed different degrees of chimeric duplications and deletions in different regions of chromosomes Y and 3. The parents were healthy and his twin brother had normal growth and development with no abnormalities at multiple follow-up visits.Neonate with incontinentia pigmenti in one of the male monozygotic twins is extremely rare and the genetic diagnosis is challenging. Awareness of the combined cerebrovascular lesions needs to be enhanced and potential prevention and treatment methods need to be explored to improve the prognosis.